Toleransi dan keberagaman di indonesia: Perspektif pluralisme dan multikulturalisme dalam kehidupan bermasyarakat - aufabrina, shadia yosvita azalie (Maliki Interdisciplinary Journal, 2026)
Indonesia is a country with a very high level of diversity, encompassing ethnic, religious, cultural, and linguistic aspects. This diversity serves as both a source of richness and a challenge in community life. This study aims to explore the contribution of tolerance to the maintenance of social harmony through the perspectives of pluralism and multiculturalism. The methodology employed is a qualitative approach using literature analysis of various relevant academic sources. The findings indicate that tolerance is a crucial element in a creating a harmonious social environment within Indonesia’s diverse society. Pluralism emphasizes the recognition of differences as a social reality, while multiculturalism promotes equal appreciation of cultural diversity. The implementation of these two concepts in societal life can strengthen unity and prevent the emergence of social conflicts. Therefore, active involvement from society, the education sector, and the government is essential in instilling the principles of tolerance, pluralism, and multiculturalism in order to achieve a peaceful and inclusive social life in Indonesia.